Terapi Eye Movement Desensitization and Reprocessing (EMDR) untuk penanganan Post Traumatic Stress Disorder (PTSD) - Annisa, Wahyu Nur (Maliki Interdisciplinary Journal, 2023)
PTSD has been a concern in various scientific investigations, because of the negative impact it causes if it is not treated immediately. Numerous research investigations have shown that long-term PTSD can lead to psychiatric illness, damage to the heart and nervous system, lower the body's metabolism, and increase the risk of suicidal behavior. These negative impacts have the potential to effectively disrupt an individual's daily life. The purpose of writing this article is to provide an overview of the concept of EMDR and how the technique can be applied to treat PTSD in clients. Eye moving desensitization and reprocessing (EMDR) can be a technique in treating post-traumatic stress disorder. It is therefore suggested that counseling practitioners in Indonesia be able to use this "unique therapy" as a technique for handling post-traumatic stress disorder. In this study a qualitative approach was used with a descriptive analytical method. Secondary data sources are used to describe systematically and accurately the data that has been collected through data processing and analysis. These sources include journals, books, news and other websites. This approach is used to provide a comprehensive explanation of how EMDR therapy is used to treat PTSD.